Refuting the hypothesis that the acquisition of germ plasm accelerates animal evolution - Carrie A. Whittle (Nature Portfolio, 2016)
The evolution of germ cell specification by maternal germ plasm has been proposed to accelerate vertebrate protein evolution by liberating selective constraints. Whittle and Extavour analyse global rates of protein evolution and find no support for this hypothesis in vertebrates or invertebrates.